Awareness Level of School Management Development Committee Members regarding their Roles and Responsibilities - Priyadarshinee, Preeti; I.P., Gowramma (JOURNAL OF INDIAN EDUCATION, 2018)
The paper examines the effectiveness of School Management and Development Committee (SMDC) by focusing on assessing the awareness level of SMDC members regarding their roles and responsibilities. By employing a descriptive survey method through a questionnaire, information was gathered from secondary schools which were purposively chosen. An interview was also conducted with the chairpersons of SMDCs, who is the head of the school. The study revealed that most of the members of SMDC are not aware about their role for the development of secondary education as prescribed by Rashtriya Madhyamik Shiksha Abhiyan (RMSA). Some members are also not aware about its meetings and most members are not oriented about their roles and responsibilities. Research also revealed that the awareness level of chairpersons of SMDCs is more than that of the other members. Orientation and capacity building programmes of all the members of SMDC by the Rashtriya Madhyamik Shiksha Abhiyan (RMSA) authority, is seen as an essential requirement in addition to prescribing a minimum educational standard for the members.